(untitled) (Research, Society and Development, 2021)
Tinnitus is considered the third most frequent otorhinolaryngological symptom on the search for medical help. It is known that tinnitus has been associated with psychiatric conditions, mainly depression and anxiety. Furthermore, the difficulty of coping with the nuisance, negatively interferes on the life quality of these patients. In clinical practice, it is not uncommon patients to refer to chronic tinnitus as a penance. A penance presupposes guilt, a symptom also related to depression. This review was designed to track studies on role of guilt in the psychism of patients with tinnitus. In this sense a bibliographic survey was done in order to analyze the possible correlations of depression, anxiety and guilt in patients with chronic tinnitus. The review draws attention to health professionals for the importance of understanding the psychism of patients with tinnitus, and to clarify their perceptions of their condition as a kind of punishment.